方程\( xy' + y = {e^x} \)在\( y(1) = e \)时可得通解中常量\( C = \)( )。______
0
举一反三
- 方程\( y' + {y \over x} = {1 \over { { x^2}}} \)在\( y(1) = 0 \)时可得通解中常量\( C = \)( )。______
- \(y=x\)方程\( y - y' = 1 + xy' \)的通解。
- 下列选项中( )是方程\( y - y' = 1 + xy' \)的通解。 A: \( y = C(x + 1) \) B: \( y = {x^2} + C \) C: \( y = x + C \) D: \( y = C(x + 1) + 1 \)
- 方程xy'-ylny=0的通解为( )。 A: y=e<SUP>cx</SUP> B: y=x C: y=e<SUP>-x</SUP> D: y=e<SUP>x</SUP>
- 3. 方程$x y' + xy = y $的通解为 A: \[y=\mathit{c}\,{{e}^{-x}}\] B: \[y=\mathit{c}x\,{{e}^{-x}}\] C: \[y=\mathit{c}x\,{{e}^{-x^2}}\] D: \[y=\mathit{c}x^2\,{{e}^{-x}}\]
内容
- 0
方程$(x^2+1)(y^2-1) + xy y' = 0$的通解为 A: $y^2 = C \frac{e^{-x^2}}{x^2}$ B: $y = C \frac{e^{-x^2}}{x^2}$ C: $y^2 = C \frac{e^{-x^2}}{x^2}+1$ D: $y=C \frac{e^{-x^2}}{x^2}+1$
- 1
方程\(\left( {1 - {x^2}} \right)y - xy' = 0\)的通解是( )。 A: \(y = C\sqrt {1 - {x^2}} \) B: \(y = - {1 \over 2}{x^3} + Cx\) C: \(y = {C \over {\sqrt {1 - {x^2}} }}\) D: \(y = Cx{e^{ - {1 \over 2}{x^2}}}\)
- 2
已知初值条件\( y(0) = 1 \),则此时\( y' + y = {x^2}{e^{ - x}} \)的通解中常量\( C = \)( )。______
- 3
方程xy'-ylny=0的通解为( )。 A: y=ecx B: y=x C: y=e-x D: y=ex
- 4
设\(z = u{e^v}\),\(u = x + y\),\(v = xy\),则\( { { \partial z} \over {\partial x}}=\) A: \({e^{xy}}(1 + xy + {y^2})\) B: \({e^{xy}}(1 + xy + {y^3})\) C: \({e^{xy}}(x+ xy + {y^2})\) D: \({e^{xy}}(y+ xy + {y^2})\)